Catalytic Asymmetric Reactions of 4‐Substituted Indoles with Nitroethene: A Direct Entry to Ergot Alkaloid Structures. Issue 49 (21st October 2015) - Romanini, Simone; Galletti, Emilio; Caruana, Lorenzo; Mazzanti, Andrea; Himo, Fahmi; Santoro, Stefano; Fochi, Mariafrancesca; Bernardi, Luca
Abstract: A domino Friedel–Crafts/nitro‐Michael reaction between 4‐substituted indoles and nitroethene is presented. The reaction is catalyzed by BINOL‐derived phosphoric acid catalysts, and delivers the corresponding 3, 4‐ring‐fused indoles with very good results in terms of yields and diastereo‐ and enantioselectivities. The tricyclic benzo[ cd ]indole products bear a nitro group at the right position to serve as precursors of ergot alkaloids, as demonstrated by the formal synthesis of 6, 7‐secoagroclavine from one of the adducts. DFT calculations suggest that the outcome of the reaction stems from the preferential evolution of a key nitronic acid intermediate through a nucleophilic addition pathway, rather than to the expected "quenching" through protonation. Abstract : Proton dance : A highly enantioselective Friedel–Crafts/nitro‐Michael reaction between 4‐substituted indoles and nitroethene, giving precursors of ergot alkaloids, is presented. Despite their acidity, phosphoric acid (PA) catalysts do not "quench" the intermediate through protonation, channeling instead the reaction through the desired domino pathway.